Improving Mathematical Connection and Motivation through the Integration of Islamic Values in Geometry Teaching Materials - Putri Yulia; Eline Yanty Putri Nasution; Anriany Casanova (Pendidikan Matematika UNIMOR, 2026)
This study focuses on how employing practical and proven Islamic values-integrated geometry teaching materials improves students' willingness to learn and their mathematical linkages to real-world situations. A pre-experimental design with a One-Group Pretest-Final test is used in the study. Total sampling was the method employed. 17 fourth-semester IAIN Kerinci math education majors participating in the Analytical Geometry course made up the study's sample. A learning motivation survey and a test of mathematical connection skills make up the data collection tools. N-Gain (Normalized Gain) and paired t-tests were used to analyze the data. The results show that the t-test's significance level is 0.002. Given that this number is less than 0.05, it confirms that Islamic Values-based educational resources are both effective and significant in enhancing students’ ability to make mathematical connections. The N-Gain analysis shows a percentage of 76%, which falls into the “effective” category. Meanwhile, the motivation score percentage of students was 75.6%, indicating that after using Islamic principles incorporated into geometry instructional materials, students exhibited high motivation to learn mathematics. This study's conclusion is that Islamic principles must be incorporated into the way mathematics is taught materials as part of a relevant and applicable instructional strategy, which positively impacts students’ mathematical connection abilities and learning motivation.